2017
DOI: 10.25279/sak.303050
|View full text |Cite
|
Sign up to set email alerts
|

Sağlik Bi̇li̇mleri̇ Fakültesi̇ Ve İkti̇sadi̇ Ve İdari̇ Bi̇li̇mler Fakültesi̇ Öğrenci̇leri̇ni̇n Yaşli Ayrimciliğina İli̇şki̇n Tutumlari

Abstract: Tutum Ölçeği kullanılmıştır. Ölçek kullanımı için Vefikuluçay'dan yazılı onay alınmıştır. Verilerin analizinde ise t-testi ve varyans analizi kullanıldı. Ayrıca Kişisel Bilgi Formu ile elde edilen bilgiler yüzde ve frekans olarak verildi. Araştırmanın sonucunda, kadın öğrencilerin erkek öğrencilere göre ve Sağlık Bilimleri Fakültesi öğrencilerinin diğer öğrencilere göre yaşlı bireylere yönelik daha olumlu tutumlara sahip olduğu saptandı. Ayrıca, ailede yaşlı bir bireyin olması, evde yaşlı bir bireyle birlikte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…18 It can be expected that young people who grow up in a nuclear family or a fragmented family have less knowledge about elderly people, are less tolerant of them, and have a different perspective. Studies by Boz et al 15 and Şahin and Erkal 11 found that the characteristics such as having an elderly person in the family, living with an elderly person at home, and encountering elderly individuals frequently increased the positive attitudes of the students towards elderly individuals. Altay and Aydın, 12 found no relationship between the students' family type and their attitudes towards elderly individuals.…”
Section: The Participating Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 It can be expected that young people who grow up in a nuclear family or a fragmented family have less knowledge about elderly people, are less tolerant of them, and have a different perspective. Studies by Boz et al 15 and Şahin and Erkal 11 found that the characteristics such as having an elderly person in the family, living with an elderly person at home, and encountering elderly individuals frequently increased the positive attitudes of the students towards elderly individuals. Altay and Aydın, 12 found no relationship between the students' family type and their attitudes towards elderly individuals.…”
Section: The Participating Studentsmentioning
confidence: 99%
“…The data were collected using a questionnaire prepared by the researchers as a result of a literature review. 5,[11][12][13][14][15][16] The questionnaire consisted of three sections and a total of 40 questions.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies are revealing that health care providers have negative and positive attitudes towards elderly individuals 10,11,[16][17][18][19] . Nurses' prejudices, values, beliefs, lack of knowledge, and negative attitudes about ageism are stated to reduce not only the quality of the care given to elderly people but also the self-esteem of elderly individuals 20,21 . Studies conducted on this subject are mostly based on quantitative data 2,3,6,8,11,13,20,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies are revealing that health care providers have negative and positive attitudes towards elderly individuals 10,11,[16][17][18][19] . Nurses' prejudices, values, beliefs, lack of knowledge, and negative attitudes about ageism are stated to reduce not only the quality of the care given to elderly people but also the self-esteem of elderly individuals 20,21 . Studies conducted on this subject are mostly based on quantitative data 2,3,6,8,11,13,20,22,23 .…”
Section: Introductionmentioning
confidence: 99%